Exploratory study of the effect of DHA supplementation on blood fatty acids and inflammatory markers in children with MIS-C - Elvira Verduci; Elvira Verduci; Patrizia Risè; Giulia Fiore; Giulia Fiore; Sara Vizzuso; Alice Bonomi; Dario Dilillo; Laura Fiori; Elisabetta Di Profio; Valeria Calcaterra; Savina Mannarino; et al. (Frontiers in Nutrition, 2025)
Background and aimsChildren infected with SARS-CoV-2 may develop multisystem inflammatory syndrome (MIS-C) 4–6 weeks after exposure. MIS-C is characterized by elevated markers of inflammation and low blood values of linoleic acid (LA), arachidonic acid (AA) and docosahexaenoic acid (DHA) during acute phase. The aim of this pilot exploratory study was to assess the short-term beneficial impact on the blood fatty acid profile following DHA supplementation in children who have suffered from MIS-C.MethodsFifty-two children aged 2–18 years with diagnosed MIS-C, were enrolled between December ‘20 and March ‘22. Blood samples were collected at hospital discharge (T0), and at 3 (T1) and 6 months (T2) post-discharge using dried blood spots for fatty acid analysis by gas chromatography. Inflammatory and metabolic blood markers were assessed at T0 and T2. All participants received healthy dietary advice throughout the study. In Group 1 23 consecutive patients received DHA supplementation (250 mg/day of DHA) from T0 to T1, followed by dietary advice alone until T2. In Group 2 29 children with MIS-C received only dietary advice throughout the observation period.ResultsAn altered inflammatory status, independent of treatment, was shown in all children compared to pediatric reference values. After intervention, Group 1 experienced a significant enrichment in both total n-6 and n-3 blood FAs when compared to baseline (p < 0.0001). Specifically, there was a significant increase of DHA (1.19 ± 0.25 at T0 vs. 2.67 ± 0.78 at T1) and EPA (0.32 ± 0.09 at T0 vs. 0.46 ± 0.10 at T1) levels, that remained consistent at T2 (p = 0.0002 and p < 0.0001, respectively). Within Group 2 only n-3 alpha linolenic acid (ALA) significantly increased at T1 compared to baseline (p < 0.05). The total increase in n-3 after intervention (ΔT1-T0) was significantly higher in Group 1 compared to Group 2 [1.90(0.9) vs. 0.49(0.8), p < 0.0001 and padj = 0.005]. Erythrocyte sedimentation rate (ESR) and IL-6 showed a better tendency toward normalization in Group 1, although without statistical significance.ConclusionThis pilot study is the first to explore the potential effects of DHA supplementation in children with MIS-C. DHA was associated with improvements in the blood fatty acid profile, which persisted beyond the supplementation period, and showed a trend toward normalization of selected biochemical parameters. Further adequately powered, controlled studies are needed to confirm these observations and to evaluate the potential role of early n-3 PUFA supplementation during the stable and recovery phases in critically ill pediatric patients.